15th Annual Fresno County Bar Association Judges' Dinner at Crossland's Barn - Watkins, Howard::::::::: (1983)
Judge Frank Creede, Jr. talking with Bernard Witkin wearing Hawaiian shirt; Ken Farnsworth playing banjo